2014
DOI: 10.1002/sec.1103
|View full text |Cite
|
Sign up to set email alerts
|

Generic constructions of secure‐channel free searchable encryption with adaptive security

Abstract: For searching keywords against encrypted data, the public key encryption scheme with keyword search (PEKS), and its an extension called secure-channel free PEKS (SCF-PEKS) have been proposed. In SCF-PEKS, a receiver makes a trapdoor for a keyword, and uploads it on a server. A sender computes an encrypted keyword, and sends it to the server. The server executes the searching procedure (called the test algorithm, which takes as inputs an encrypted keyword, trapdoor, and secret key of the server). In this paper,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Comparison and analysis show that our semi‐generic edPEKS construction introduces very few additional costs to enhance the underlying dPEKS scheme to obtain the security against all the exiting known types of KG attacks. We note that if applying our method to the previous generic dPEKS constructions, then we will get several new semi‐generic edPEKS constructions that are based on some more normal cryptographic primitives, such as (anonymous) IBE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparison and analysis show that our semi‐generic edPEKS construction introduces very few additional costs to enhance the underlying dPEKS scheme to obtain the security against all the exiting known types of KG attacks. We note that if applying our method to the previous generic dPEKS constructions, then we will get several new semi‐generic edPEKS constructions that are based on some more normal cryptographic primitives, such as (anonymous) IBE.…”
Section: Discussionmentioning
confidence: 99%
“…Following the proposal of Baek et al, lots of dPEKS schemes were presented . In addition, the generic dPEKS constructing methods were also proposed . Rhee et al showed that a dPEKS scheme can be generically derived by combining two IBE schemes in parallel or in sequence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also presented an SCF-PEKS scheme secure under the enhanced security model in the random oracle model. Another extension on SCF-PEKS is by Emura et al [5]. They enhanced the security model by introducing the adaptively secure SCF-PEKS, wherein an adversary is allowed to issue test queries adaptively.…”
Section: B Secure Channel Free Peksmentioning
confidence: 99%
“…Fang et al [6] proposed a concrete SCF-PEKS scheme with KGA resilience. Similar to the work in [5], they also considered the adaptive test oracle in their proposed security definition.…”
Section: Against Outside Kgamentioning
confidence: 99%